Early adjustment of empirical antibiotic therapy of bloodstream infections on the basis of direct identification of bacteria by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and Gram staining results. Issue 9 (September 2020) - Torres, Ignacio; Pinto, Carolina; Oltra, Rosa; Pascual, Tania; Carbonell, Nieves; Colomina, Javier; Tormo, Mar; Albert, Eliseo; Aguilar, Gerardo; Solano, Carlos; Navarro, David
Abstract: Introduction: To assess the potential added value of rapid MALDI-TOF MS-based identification of bacteria in positive blood cultures to the information provided by Gram staining for adequate empirical antibiotic treatment adjustments in patients with bloodstream infections (BSI). Methods: We conducted a retrospective, single-center, pre-post quasi-experimental study. In the pre-MALDI-TOF MS phase of the study antibiotic adjustments were made on the basis of Gram stain results, whereas in the MALDI-TOF MS phase they were based on information provided by Gram staining and MALDI-TOF MS results. No antimicrobial stewardship program for BSI was in place within the study period. Antibiotic regimens were categorized as correct, improvable or incorrect. Results: Cohorts were matched for demographics, clinical characteristics of patients and bacterial species involved. Enterobacteriales were the most represented in both study periods (67%), followed by Non-fermenting Gram-negative bacilli and Gram-positive cocci. The number of patients receiving correct, improvable and incorrect empirical antibiotic treatments was comparable for both study periods ( P  = 0.45, P  = 0.57, P  = 0.87, respectively). The percentage of patients who ended up receiving correct treatment following modified empirical antibiotic regimens was significantly higher ( P  = 0.008) in the MALDI-TOF MS phase (27 patients/38.6%) than in the pre-MALDI-TOF MS phase of the study (11 patients/15.7%), although overall adequate coverage of the bacteria causing the infection was comparable across the study periods (90%). Conclusion: Gram stain results offer valuable information for early adjustment of empirical antibiotic therapies for BSI. Nevertheless, rapid identification of bacteria involved in BSI by MALDI-TOF MS provides added value to achieve this aim.